2010
DOI: 10.1186/ar3159
|View full text |Cite
|
Sign up to set email alerts
|

Does moderate-to-high intensity Nordic walking improve functional capacity and pain in fibromyalgia? A prospective randomized controlled trial

Abstract: IntroductionThe objective of this study was to investigate the effects of moderate-to-high intensity Nordic walking (NW) on functional capacity and pain in fibromyalgia (FM).MethodsA total of 67 women with FM were recruited to the study and randomized either to moderate-to-high intensity Nordic Walking (n = 34, age 48 ± 7.8 years) or to a control group engaging in supervised low-intensity walking (LIW, n = 33, age 50 ± 7.6 years). Primary outcomes were the six-minute walk test (6MWT) and the Fibromyalgia Impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
167
1
14

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(187 citation statements)
references
References 25 publications
5
167
1
14
Order By: Relevance
“…The FM patients in the present study were only able to perform exercise up to an average of 82 W before the rated exertion achieved extreme levels while the healthy control group maintained the ability to continue performing up to an average of 122 W. This observation implies that FM patients may experience difficulty in the performance of particular physical activity and exercise programs designed for healthy women. For FM patients to be able to exercise on a moderate to high intensity (the Borg scale: RPE 15) without increased pain, 2 minute interval training has been shown to be appropriate [40].…”
Section: Hrmentioning
confidence: 99%
“…The FM patients in the present study were only able to perform exercise up to an average of 82 W before the rated exertion achieved extreme levels while the healthy control group maintained the ability to continue performing up to an average of 122 W. This observation implies that FM patients may experience difficulty in the performance of particular physical activity and exercise programs designed for healthy women. For FM patients to be able to exercise on a moderate to high intensity (the Borg scale: RPE 15) without increased pain, 2 minute interval training has been shown to be appropriate [40].…”
Section: Hrmentioning
confidence: 99%
“…In our study training speed was in general very low, in studies with medium effects group worked with patients who had abilities to participate in a high intensity Nordic walking program (Mannerkorpi et al, 2010). Therapists should work with patients at a maximum of intensity, if they decide to apply a Nordic walking program.…”
Section: Discussionmentioning
confidence: 85%
“…Those studies evaluating medium to high training intensities reported large or medium effect sizes (Long & Van Stavel, 1995;Mead et al, 2010;Mannerkorpi et al, 2010). The participants in these studies were less affected by their complaints or had no or few co-morbidities (Long & Van Stavel, 1995;Mead et al, 2010;Hartvigsen, Morsø, Bendix, & Manniche, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations